Metal nanoparticles and related materials supported on carbon nanotubes: methods and applications. - Wildgoose, G; Banks, C; Compton, R (2006)
Carbon nanotubes are one of the most intensively explored nanostructured materials. In particular, carbon nanotubes are unique and ideal templates onto which to immobilize nanoparticles allowing the construction of designed nanoarchitectures that are extremely attractive as supports for heterogeneous catalysts, for use in fuel cells, and in related technologies that exploit the inherent 'smallness' and hollow characteristics of the nanoparticles. Here we overview the recent developments in this area by exploring the various techniques in which nanotubes can be functionalized with metals and other nanoparticles and explore the diverse applications of the resulting materials.